Pengaruh Kemudahan, Kepercayaan Dan Manfaat Terhadap Minat Bertransaksi Menggunakan Dompet Digital Ovo Di Yogyakarta - Iwan Kusuma, Deden; Belinda Tolat, Almira (GEMA EKONOMI, 2023)
This study aims to analyze the effect of perceived convenience, perceived trustworthiness and perceived benefits on requesting transactions using the OVO digital wallet. This research uses a quantitative approach by collecting data through the survey method. The population in this study were Yogyakarta students who had transacted using the OVO digital wallet. Sampling using the purposive sampling method with criteria that have been transacted using the OVO digital wallet. The sample in this study amounted to 110 respondents obtained from the distribution of questionnaires. The data analysis technique of this study uses descriptive analysis techniques and multiple linear regression. The results of this study show that: Perception of convenience, Perception of trust and Perception of benefits have a positive effect on the interest in transacting using the OVO digital wallet